Frontiers in quantum methods and applications in chemistry and physics : selected proceedings of QSCP-XVIII (Paraty, Brazil, December, 2013) /: selected proceedings of QSCP-XVIII (Paraty, Brazil, December, 2013). ([2015]) - Unknown
No abstract available